Training the Application of Financial Management and Communication Knowledge in Sumenep Amplang Crackers UMKM - Rizal, Saiful; Hidayati, Nur; Basalamah, M. Ridwan (Journal of Educational Sciences, 2025)
UD Sun is A business micro small and medium enterprises (SMEs) located in Kartasada, Kalianget, Sumenep City. UD Matahari focus on production shrimp crisp amplang, which has mark high sales and profits. Problems faced MSME actors are Not yet existence training management finance business use application in a way directly. The solution needed is counseling and mentoring for MSME actors in managefinances. Research This own objective is For do mentoring or training to be able to apply management finance and science communication with Good use repair management orderly finances in this UMKM. The method used is descriptive with technique observation, companion, and evaluation. Research results This show that training and mentoring knowledge management finance and science communication in UMKM Crackers Amplang Sumenep show that A deeper understanding Good about management finance more understand importance recording finance and start take notes transaction in a way regular and able make report finance simple, like report profit loss. This helps management understand cash flow and determine profit or losses, as well as plan expenses and income with more okay. Then increase communication effective business and capabilities more communication good, polite and friendly to customer.